2023
DOI: 10.3390/agriculture13030733
|View full text |Cite
|
Sign up to set email alerts
|

Swine Breeding in the Villages of Vâlcea County, Oltenia (Romania)—Tradition or Necessity?

Abstract: Food supply has been a constant source of concern for mankind. In the present context, with food security a priority of European and national policies, an analysis of pig farming in a representative NUTS2 administrative level of Romania that emphasizes the proportion of households raising at least one pig and the main factors influencing farmers to adopt or give up swine breeding could allow a much clearer understanding of this phenomenon that lies at the border between cultural tradition and socio-economic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Local consumers are attracted by traditional themed restaurants that advertise the origins and authenticity of their products, appealing to consumers' emotions, familiar memories, and nostalgic feelings [57][58][59]. Studies have shown that autochthonous consumers prefer familiar dishes and are ethnocentric in their support for authentic products [60], as also demonstrated by dietary behavior maintaining large-scale subsistence family farming in Romania [61] and Bucharest foodies in search of multisensory experiences in venues around the Romanian capital city [62]. Both locals and tourists feel the need to connect with local food and to be informed of its provenance, considered a distinctive characteristic of gastronomic products [63].…”
Section: Traditional Food a Source Of Well-being That Generates Pleas...mentioning
confidence: 99%
“…Local consumers are attracted by traditional themed restaurants that advertise the origins and authenticity of their products, appealing to consumers' emotions, familiar memories, and nostalgic feelings [57][58][59]. Studies have shown that autochthonous consumers prefer familiar dishes and are ethnocentric in their support for authentic products [60], as also demonstrated by dietary behavior maintaining large-scale subsistence family farming in Romania [61] and Bucharest foodies in search of multisensory experiences in venues around the Romanian capital city [62]. Both locals and tourists feel the need to connect with local food and to be informed of its provenance, considered a distinctive characteristic of gastronomic products [63].…”
Section: Traditional Food a Source Of Well-being That Generates Pleas...mentioning
confidence: 99%
“…This literature review allows the author to state that a substantial share of recent academic contributions on structural changes in pig farming covers socioeconomic aspects and comes from countries that joined the EU in 2004 and later. These MSs have faced the unprecedented evolution of the national livestock sector (for example, see [6][7][8][9][10][11]). The strong focus on environmental concerns and climate change mitigation arises from the pre-2004 MSs because most of these MSs have developed a highly concentrated production system and provide remarkable contributions to GHGEs due to EU pig farming.…”
Section: Introductionmentioning
confidence: 99%
“…[1, 3,4] whereby it contributes to an integrated development in a regional rural economy, through interconnections with other sectors of economic activity [5][6][7][8] and by reducing poverty levels [3]. The impact of agriculture on the socio-cultural aspects is also recognized-i.e., the influence of farming practices on the lifestyle of the inhabitants of the area and their local culture [1, 7,9,10]. Furthermore, agriculture represents more than a practical economic activity in rural environments; it is considered a way of living, knowing, and creating a distinct region from the urban areas.…”
mentioning
confidence: 99%
“…Furthermore, agriculture represents more than a practical economic activity in rural environments; it is considered a way of living, knowing, and creating a distinct region from the urban areas. Thus, farmers are considered holders of knowledge and guardians of traditional practices and natural and cultural heritage in the countryside [1,10]. However, at the same time, agriculture has a strong impact on the environment, resulting from strong impact on the environment, which occurs because of the intensification and expansion of agricultural lands [1,7,11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation